HIGHER EDUCATION OF SWEDEN: EUROPEAN STANDARDS AND SCANDINAVIAN STYLE - ZHELANOV , DMYTRO (Journal of Vasyl Stefanyk Precarpathian National University, 2019)
The article analyzes certain aspects of the development of higher education in Sweden in the context of modern globalization and integration of socio-economic processes in the countries of the European Union. The article studies the position regarding the features of modern higher education, connected with its output beyond the limits of individual states and transformation into an international institution. It is proved that this circumstance determines significant achievements in the integrated development of the European higher education, leaving, at the same time, the risks of losing its national features and dropping the level of higher education in countries that are not well targeted for the welfare of the population. The necessity of taking into account the essence of these risks has been substantiated in order to increase the competitiveness of Ukrainian higher education institutions in their interrelation and cooperation with universities of Europe. The expediency of studying and introducing the best foreign experience in the national higher education system of the Scandinavian countries in particular and, namely, of Sweden, has been proved.